Pd Reaction Intermediates in Suzuki‐Miyaura Cross‐Coupling Characterized by Mass Spectrometry. Issue 3 (3rd February 2022) - Chen, Xingshuo; Wei, Zhenwei; Huang, Kai‐Hung; Uehling, Mycah; Wleklinski, Michael; Krska, Shane; Makarov, Alexey A.; Nowak, Timothy; Cooks, R. Graham
Abstract: Palladium‐catalyzed Suzuki‐Miyaura (SM) coupling is widely utilized in the construction of carbon‐carbon bonds. In this study, nanoelectrospray ionization mass spectrometry (nanoESI‐MS) is applied to simultaneously monitor precatalysts, catalytic intermediates, reagents, and products of the SM cross‐coupling reaction of 3‐Br‐5‐Ph‐pyridine and phenylboronic acid. A set of Pd cluster ions related to the monoligated Pd (0) active catalyst is detected, and its deconvoluted isotopic distribution reveals contributions from two neutral molecules. One is assigned to the generally accepted Pd(0) active catalyst, seen in MS as the protonated molecule, while the other is tentatively assigned to an oxidized catalyst which was found to increase as the reaction proceeds. Oxidative stress testing of a synthetic model catalyst 1, 5‐cyclooctadiene Pd XPhos (COD−Pd‐XPhos) performed using FeCl3 supported this assignment. The formation and conversion of the oxidative addition intermediate during the catalytic cycle was monitored to provide information on the progress of the transmetalation step. Abstract : Pd (0) reaction intermediates in Suzuki‐Miyaura cross coupling captured and characterized by mass spectrometry is reported in this work. Deconvoluting the isotopic distribution of the ion cluster due to the monoligated active catalyst reveals contribution of three ions corresponding to a low valent form (protonated and radical cation) and an oxidized form of the active catalyst.